Novel agents in treatment of acute myeloid leukemia - Gil, Lidia; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2007)
Current treatment strategies of acute myeloid leukaemia based on conventional cytotoxic agents provide complete remission in 60%-80% of younger patients; however, only 30%-40% are alive at 5 years. For elderly patients significant improvements in survival have not emerged for years. Most recently, insights into the molecular pathogenesis of AML have led to the development of specific targeted therapy. This review presents new drugs being studied alone or in combination with chemotherapy: immunoconjugate gemtuzumab ozogamicin, multidrug resistance inhibitors, farnesyl transferase inhibitors, FLT3 inhibitors, antiangiogenic agents, apoptosis modulators, epigenetic agents and new nucleoside analogues and alkylating agent